Income disparity among older Malaysians - Masud, Jariah; Haron, Sharifah Azizah (Macrothink Institute, 2014)
The aim of this paper is to explore income disparities among older Malaysians. The specific objective is to determine the income disparities among different groups by gender, ethnicity, stratum and region. A total of 2,327 Malaysians, ages 55 to 75, were interviewed for the study. The data show that primary sources of income for older Malaysians, women in particular, were their children. The income disparity among various groups of older Malaysians was rather wide. Men tended to earn higher incomes compared to women. There were income gaps by ethnicity, strata, and region. The income gap among the participants in this study was much wider compared to the general population. The disparity reflected differences in the older persons’ ability to meet daily needs, highlighting the need for programs designed specifically to address poverty among older Malaysians.